The Influence of Management Accounting Information, Product Innovation, and Strategic Management Accounting on MSME Performance With Competitive Advantage as an Intervening Variable - Ahmad Ellen Saputro; Novi Darmayanti; Have Zulkarnaen (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of management accounting information, product innovation, and strategic management accounting on the performance of Micro, Small, and Medium Enterprises (MSMEs), with competitive advantage acting as an intervening variable. MSMEs play a significant role in supporting economic growth; however, they continue to face various challenges, including limited resources, increasingly intense business competition, and rapidly changing business environments. These conditions require MSME actors to effectively manage business information and strategies in order to improve their organizational performance. This research employs a quantitative approach using a survey method by distributing questionnaires to MSME actors who serve as the respondents of the study. The sampling technique applied in this research is purposive sampling, where respondents are selected based on specific criteria relevant to the objectives of the study. The collected data are analyzed using statistical analysis methods to examine the relationships among management accounting information, product innovation, strategic management accounting, competitive advantage, and MSME performance. The results of this study are expected to provide empirical evidence regarding the importance of utilizing management accounting information, developing product innovation, and implementing strategic management accounting in enhancing competitive advantage and improving MSME performance. Furthermore, this study is expected to contribute to the development of management accounting knowledge and serve as a reference for MSME practitioners in improving business performance in a sustainable manner.